Robert Duncan’s Big Poetry: Re-visioning the Common - Miriam Nichols (Sillages Critiques)
This article takes breadth to be the central fact to Robert Duncan’s poetry. It argues for a reading of Duncan’s work from the perspective of his yearning for synthesis, while acknowledging that the “grand collage” Duncan evokes must remain out of reach. It is this daring scope, with its own excesses and distortions, that accounts for the multiple challenges Duncan’s work continues to pose to his readers. This article suggests a different understanding of measure in Duncan – an ethical and methodological one, rather than a strictly formal or prosodic one. Duncan’s purpose is at once political, moral and aesthetic, directed toward the articulation of human collectivity, despite the recognition that modern societies are fraught with social and cultural difference.